CONFLICT AND VIOLENCE PREVENTION AT WORK PLACES: IS IT THE GRASS THAT SUFFERS? EFFECTS OF CONFLICT AND VIOLENCE ON INDIVIDUAL AND ORGANISATIONAL PERFORMANCE IN ZIMBABWE - Gwakwa, Milton (European Scientific Journal, ESJ, 2015)
Management of conflict and the prevention of violence at workplaces is a key practice among the 20st century organisations. The purpose of this study was to interrogate, the conflict phenomenon in Zimbabwe with a view to provide sustainable conflict management solutions, given its negative impact on organisational productivity and individual performance if not properly managed. The study was both qualitative and quantitative in design. A total of 54 companies were interviewed through in-depth interviews, questionnaires and observations. The results of the study indicate that conflict was rife in Zimbabwe organisations and that it was counterproductive, especially for those companies that did not have conflict management policy. Data was analysed statically using Pearson’s correlation analysis and thematically. The recommendation is that there is need to embrace a conflict management model that cuts across national, industrial, organisational and individual levels.